Strategic-Based Approach in Developing of Tourism in the Context of Modeling Structural Changes in the Regional Economy - E. G. Leonidova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The goal of this study is a need for scientific substantiation of the use of a strategic approach to the development of the tourism sector in the region, considered as the direction of structural changes in the economy. For achieving this goal it is necessary to explore the existing approaches to strategizing, analyze the experience of strategic management of tourism in the regions, determine ways to developing this sphere. The novelty of this study consists in the formation of strategic areas of develop